Land cover changes in the Upper Great Ruaha (Tanzania) and the Upper Awash (Ethiopia) river basins and their potential implications for groundwater resources - Chandrasekharan, Kiran M.; Villholth, Karen G.; Kashaigili, J. J.; Gebregziabher, Gebrehaweria; Mandela, P. J. (International Water Management Institute, 2023)
Over the past century, the world has experienced an unprecedented surge in population growth, accompanied by a significant increase in economic activity and fuelled by an intensive utilization of natural resources, including water. This phenomenon has brought about profound alterations in land cover and land use patterns across various regions. Knowledge of land use changes is key to unlocking an understanding of water use changes and associated impacts on water resources, and potential threats to sustainability. However, the pace and nature of land use transitions vary widely across the globe, shaped by a complex interplay of local, regional and global factors, making systematic assessments important. This report presents the results of a land cover change analysis conducted in two river basins in sub-Saharan Africa: the Upper Great Ruaha River Basin (UGRRB) in Tanzania and the Upper Awash River Basin (UARB) in Ethiopia. The spatio-temporal analysis spans a recent 15-20-year period up until 2015/16 and utilizes remote sensing imagery, secondary maps and ground truth information for the two end point times (resolution: 30 m). The basins are significantly different in terms of agricultural development and water resource use. UARB represents an area with emerging commercial farms, urban expansion and diminishing natural vegetation, whereas UGRRB still retains significant natural vegetation but is experiencing an increase in smallholder agriculture as well as intensive commercial irrigation potentially affecting fragile wetland systems. In UGRRB, surface water is the main source of irrigation water, while in UARB, groundwater resources are increasingly used for irrigation by smallholder farmers. The findings reveal a common overall trend in both basins that is similar to many low-income countries, illustrating an expansion of agricultural and irrigated areas and human settlements at the expense of natural land cover. The report presents a detailed systematic remote sensing-based methodology to quantify and compare land cover transitions in time and space with high resolution, within and between agricultural landscapes of larger basins. The study highlights that land cover changes in the basins follow diverse and unique trajectories, providing critical insights into evolving land use patterns. In its conclusion, the study underscores the profound implications of recent land use changes for groundwater resources within these agro-pastoral systems. Overall, the report highlights the importance of sustainable land management and integrated water resources management, and provides valuable insights into the complexities of land use change in these regions.